Check sibling questions

Ex 14.4, 13 - Find and correct (2a + 3b) (a - b) = 2a^2 - 3b^2

Ex 14.4, 13 - Chapter 14 Class 8 Factorisation - Part 2


Transcript

Ex 14.4, 13 Find and correct the errors in the following mathematical statements. (2a + 3b) (a – b) = 2π‘Ž^2 – 3𝑏^2 (2a + 3b) (a – b) = 2π‘Ž^2 – 3𝑏^2 Solving L.H.S : (2a + 3b) (a – b) = 2a (a βˆ’ b) + 3b (a βˆ’ b) = (2a Γ— a) βˆ’ (2a Γ— b) + (3b Γ— a) βˆ’ (3b Γ— b) = γ€–2π‘Žγ€—^2 βˆ’ 2ab + 3ba βˆ’ γ€–3𝑏〗^2 = γ€–2π‘Žγ€—^2 βˆ’ 2ab + 3ab βˆ’ γ€–3𝑏〗^2 Taking ab common = γ€–2π‘Žγ€—^2 + ab (βˆ’2 + 3) βˆ’ γ€–3𝑏〗^2 (Since 3ba = 3ab) = γ€–2π‘Žγ€—^2 + ab βˆ’ γ€–3𝑏〗^2 ∴ (2a + 3b) (a βˆ’ b) = γ€–πŸπ’‚γ€—^𝟐 + ab βˆ’ γ€–πŸ‘π’ƒγ€—^𝟐 is the correct statement

Davneet Singh's photo - Teacher, Engineer, Marketer

Made by

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 12 years. He provides courses for Maths and Science at Teachoo.